Biodiversity in Managed forests - Chaturvedi, A. N. (Indian Forester, 1994)
Biological diversity or biodiversity as is commonly called is an ill-defined concept. There are various varying estimates of the biological diversity. Biodiversity may be in terms of species of flora and fauna or in terms of varieties within species. The tropical rain forests contain the maximum number of species. The temperate forests due to more restricted climatic conditions and small growing season contain fewer species. Since the objectives of preservation of biodiversity are not clear cut, the economics varies with the concept.A1l species are not valuable at present. What will become valuable in future is unknown. Consequently, the exact objective of a biosphere reserve remain vague Ex -situ conservation is extremely expensive and can be carried out only on plants of known economic value. In-Situ conservation is, therefore, cheaper and more meaningful. The exploding population of human beings and livestock are degrading the eco-system and are the main cause of deforestation which has increased over the last decade. The FAO Tropical Action Plan did provide some directions for meaningful biodiversity. These are in any case very loose pronouncements. Every nation will have to fix its priorities. Whenever any area is closed to local and commercial use, some species try to dominate the floor. This, however, is a short term occurrence till the ecological Succession gets going. The biggest problem in all biodiversity areas is to keep the biotic pressure out of these areas. Protecting the biodiversity is a gigantic task in India considering that livestock population is presently around 450 million while the carrying capacity of the grazing land and forests is not more than 50 million heads. Management for biodiversity will first need very clear objectives which will not change during the next century.